ANALISIS PERILAKU NASABAH PRIORITAS TERHADAP INVESTASI DEPOSITO (STUDI pada BANK TABUNGAN NEGARA KANTOR CABANG MALANG) - Nadya Aryani Laksana Putri; Nurul Badriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Asset management can be done in several sectors such as banking . The bank intermediary institutions between the excess funds to those who need funds offering deposit products as low-risk investment products . However, many factors that become the background of customers choose a bank to entrust the assets and deposits as a form of investment that is taken . Then the research conducted by interview and direct observation on customers prioriatas Bank BTN Branch Malang . It aims to find the factors that influence the behavior of customers priority in investing deposits. The results showed that convenience is one factor customers choose a bank , while the principle of trust , low-risk factors and special aspects affecting the rate of customer behavior in investing deposits. Keywords : Deposit, Bank, Trust